Pengembangan Ekonomi Pada Lima Pesantren Kabupaten Lamongan, Jawa Timur - Achmad Dudin (Badan Litbang dan Diklat Kementerian Agama RI, 2013)
This writing isthe result of research on economic development in 5 Islamic boarding schools (pesantren) in Lamongan, East Java, 2010. This research is rooted in the context of economic development among the people, as Islamic boarding schools are challenged with improving standards of living in the form of business activities, including the potential human resources in local communities. The objective of the research was to support the Islamic boarding school in economic development through supervision. This research applied several methods including: selecting 5 Islamic boarding schools by the team to be executors of the program and financial support for orientation activities focused on the funding and business development of animal husbandry, as well as the execution of supervising, monitoring, evaluating, and reflecting on the program in order to reach the target of Islamic boarding school economic development. The result is the increase in the economic management and development of the Islamic boarding school. Tulisan ini merupakan hasil penelitian terapan tentang pengembangan potensi ekonomi pesantren pada 5 pesantren di Lamongan Jawa Timur tahun 2010. Penelitian ini dilatarbelakangi oleh kenyatanan bahwa dalam konteks pengembangan ekonomi masyarakat, pesantren dihadapkan pada upaya peningkatan taraf hidup dan kesejehateraan masyarakat dalam bentuk kegiatan usaha yang dimulai dengan penelaahan potensi dan pelu- potensi dan peluang usaha yang dimiliki, termasuk potensi SDM dengan melibatkan masyarakat setempat. Tujuan penelitian ini adalahmembantu pesantren dalam mengembangkan potensi ekonomi melalui program pendampingan. Dalam penelitian ini dilakukan beberapa tahapan antara lain, studi kelayakan yang menetapkan 5 pondok pesantren sebagai pelaksana program, kegiatan orientasi yang difokuskan pada usaha pengembangan penggemukan sapi dan pemberian dana pengembangan dan replikasi, serta kegiatan supervisi, monitoring, evaluasi, dan refleksi demi tercapainya usaha pengembangan ekonomi pesantren. Hasilnya terdapat peningkatan mutu pengelolaan dan pengembangan ekonomi pesantren.